Effect of propylene glycol on in vitro LPS activation of rat peritoneal macrophage - SAINI, M; GUPTA, L K; MALIK, S V S; SHARMA, BHASKAR (The Indian Journal of Animal Sciences, 2014)
Propylene glycol (PG), a relatively nontoxic industrial solvent and a common feed additive for cows, decreased the phagocytic index of Listeria monocytogenes significantly (P